Prototype Constitutional Supervision in China: The Lessons of the Hong Kong Basic Law Committee. Issue 2 (23rd March 2016) - IP, Eric C.
Abstract: Recurrent proposals to establish a constitutional supervisory committee have been pertinaciously rejected in spite of widespread recognition of the Chinese Constitution's ineffectiveness. And yet, the Hong Kong Basic Law Committee has long epitomized in practice a prototypic form of constitutional supervision. Vested with quasi-judicial competences, the Committee seemed destined for a central role under the "One Country, Two Systems" arrangement. The tight secrecy imposed on its proceedings and the suppression of its potential to act consistently and with a distinct identity have fatally undermined the Committee's ability to modulate constitutional tensions by way of coordinating expectations of the Basic Law's proper meaning. The experience of the Basic Law Committee reveals the recalcitrance of the Party-state toward constitutional interpretation by any specialized body, even one whose powers are heavily circumscribed and whose membership is tightly controlled.